CAMAM: A Miniature Laser Ablation Ionisation Mass Spectrometer and Microscope‐Camera System for In Situ Investigation of the Composition and Morphology of Extraterrestrial Materials. Issue 4 (December 2014) - Tulej, Marek; Riedo, Andreas; Neuland, Maike B.; Meyer, Stefan; Wurz, Peter; Thomas, Nicolas; Grimaudo, Valentine; Moreno‐García, Pavel; Broekmann, Peter; Neubeck, Anna; Ivarsson, Magnus
<x xml:space="preserve">Abstract</x> Performance studies of a microscope‐camera system (MCS) and a laser ablation/ionisation mass spectrometer (LIMS) instrument (referred to here as a laser mass spectrometer or LMS) are presented. These two instruments were designed independently for in situ analysis of solids on planetary surfaces and will be combined to a single miniature instrument suite for in situ chemical and morphological analysis of surface materials on planetary bodies. LMS can perform sensitive chemical (elemental, isotope and molecular) analyses with spatial resolution close to micrometre‐sized grains. It allows for studies with mass resolution (M/ΔM) up to 800 in ablation mode (elemental composition) and up to 1500 in desorption mode (molecular analysis). With an effective dynamic range of at least eight orders of magnitude, sensitive and quantitative measurements can be conducted of almost all elements and isotopes with a concentration larger than a few ppb atoms. Hence, in addition to the major element composition, which is important for the determination of mineralogical constituents of surface materials, trace elements can also be measured to provide information on mineral formation processes. Highly accurate isotope ratio measurements can be used to determine in situ geochronology of sample material and for investigations of various isotope fractionation processes. MCS can conduct optical imagery of mm‐sized objects at several wavelengths with micrometre spatial resolution for the characterisation of morphological surface details and to provide insight into surface mineralogy. Furthermore, MCS can help in the selection of sample surface areas for further mass spectrometric analysis of the chemical composition. Surface auto‐fluorescence measurements and images in polarised light are additional capabilities of the MCS, to identify either fluorescing minerals or organic materials, if present on the analysed surface, for further investigation by LMS. The results obtained by investigations of NIST reference materials, amino acid films and a natural graphite sample embedded in silicate rock are presented to illustrate the performance of the instruments and their potential to deliver chemical information for mineral and organic phases in their geological context.